An experimental study of the water-holding and strength characteristics of unsaturated canal embankment soils in the South-to-North water diversion project - Wang, Dubo; Wang, Chuang; Wang, Zirui (Frontiers in Earth Science, 2025)
The water-holding and strength characteristics of unsaturated expansive soil and modified soil in a high-fill canal embankment along the central line of the South-to-North Water Diversion Project were investigated using a pressure plate apparatus and a GDS unsaturated triaxial test system. The soil-water characteristic curves (SWCCs) of expansive soil and modified soil were obtained by curve-fitting the results of water-holding characteristic tests, thereby revealing the distinctions in water-holding characteristics of the two soil types. The laws governing the effects of matrix suction on the stress-strain relationships and shear strength of the two soil types were explored through unsaturated triaxial drainage shear tests. According to the test results: (1) The moisture content and void ratio of each soil type decreased gradually with the increase in matrix suction, although the void ratio of modified soil decreased at a slower rate than that of expansive soil. (2) Matrix suction induced a transition from strain hardening to strain softening; (3) The shear strength of both soils increases with the matrix suction and confining pressure, with the increment of expansive soil greater than that of modified soil. Notably, the influence of confining pressure became progressively more significant with increasing matrix suction for both soils; (4) The cohesion and internal friction angle of expansive soil and modified soil increases with the matrix suction, with 200 kPa as the critical point of increasing rate; (5) The expansive soil differs from modified soil in cohesion and internal friction angle under different matrix suctions, with matrix suction of 400 kPa as the critical point. (6) The matrix suction thresholds of 200 kPa and 400 kPa can serve as references for engineering design and construction, as well as seepage prevention and slope reinforcement. This study provides technical parameters and theoretical support for the design, construction, and long-term stability of embankments on the expansive soil in the South-to-North Water Transfer Project site.